Hubungan antara Mobbing dengan Adversity Quotient Siswa SMK DKI Jakarta - Rachmah, Yuniar Siti; Yulia, Cici; Natalia, Nory (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
This study aims to examine the relationship between mobbing and adversity quotient (AQ) among vocational high school students (SMK) in the DKI Jakarta area. A quantitative correlational approach was used, with Spearman’s rank correlation test employed to measure the relationship between the mobbing variable and adversity quotient. The mobbing variable in this study was assessed using five indicators: effects on self-expression and communication, social contact, personal reputation, work situation and quality of life, and physical health. Meanwhile, AQ was measured using four indicators: control, origin & ownership, reach, and endurance. The Spearman correlation test results indicated a significant positive relationship between mobbing and adversity quotient (r = 0.583, p < 0.01). These findings suggest that the higher the level of mobbing experienced by students, the greater the challenges they face in maintaining psychological resilience. This result can serve as a need assessment basis for guidance and counseling teachers in designing preventive interventions focused on strengthening students' resilience in dealing with social pressure. The findings also provide valuable insight for educators in fostering a safe, emotionally healthy, and mentally supportive learning environment.